Evaluation of the clinical effect of inflatable mediastinoscopy synchronous laparoscopic radical resection of esophageal cancer: a comparative study - Hai-Tao Wei; Sa Zhang; Yang-Yang Liu; Hai-Feng Zhang; Xiao-Long Wang; Li Li (European Journal of Medical Research)
Abstract Objective To explore the technical innovation and clinical application effect of inflatable mediastinoscopy synchronous laparoscopic radical resection of esophageal cancer. Methods The clinical data of 180 patients with esophageal cancer treated by the same surgical team from January 2018 to December 2019 were retrospectively analyzed. The patients were divided into the inflatable mediastinoscopy synchronous laparoscopic group (n = 93) and the McKeown group (n = 87) according to the surgical approach. Preoperative general baseline data, perioperative indices, postoperative indices, and short- and long-term survival rates were recorded and statistically analyzed for both groups. Results Compared to McKeown’s procedure, the inflatable mediastinoscopy synchronized laparoscopic esophagectomy was associated with relatively less operative time, blood loss, and hospital stay, specifically (94.46 ± 20.17) minutes, (36.76 ± 16.63)ml, and (13.63 ± 2.57) days, respectively. At the same time, the postoperative complication rate of the inflatable mediastinoscopy synchronized laparoscopic esophagectomy was low compared to the postoperative complication rate of McKeown's procedure. Conclusion Compared with the traditional McKeown procedure, the patients treated with inflatable mediastinoscopy synchronous laparoscopic radical resection of esophageal cancer have a lower incidence of thoracic complications, shorter operation time, less pain, and faster postoperative recovery so that it can be used as a new supplementary method for mainstream McKeown radical resection of esophageal cancer.